College students' daily coping, mood, and quality of life: Benefits of problem‐focused engagement. (29th November 2018) - Shermeyer, Leaha; Morrow, Michael T.; Mediate, Nicholas
Abstract: In this short communication, we investigated the relations of daily coping, mood, and quality of life in college students ( n = 74) over seven consecutive days ( n = 510). Specifically, we tested whether four types of daily coping (problem‐focused engagement, problem‐focused disengagement, emotion‐focused engagement, and emotion‐focused disengagement) were associated with three aspects of daily functioning (negative mood, positive mood, and quality of life). In a single multilevel multivariate regression model, we examined the day‐to‐day relations of the four coping strategies with mood and quality of life, while controlling for perceived stress. Results largely supported our hypotheses, such that problem‐focused engagement was linked to lower negative mood and higher positive mood and quality of daily life, whereas the three other types of coping were negatively related or unrelated to daily functioning. These findings provide support for the benefits of problem‐focused engagement in coping with everyday stressors of life as a college student, and implications for psychotherapy and counselling are discussed.